Dreyfusia nordmannianae in Northern and Central Europe: potential for biological control and comments on its taxonomy. (1st November 2012) - Ravn, H. P.; Havill, N. P.; Akbulut, S.; Foottit, R. G.; Serin, M.; Erdem, M.; Mutun, S.; Kenis, M.
Abstract The silver fir woolly adelgid, Dreyfusia nordmannianae, is the most severe pest occurring on Abies nordmanniana in Central and Northern Europe. The adelgid is particularly damaging to trees in Christmas tree plantations. Dreyfusia nordmannianae is native to the Caucasus region and alien to Europe, where its natural enemy complex is less diverse compared to its area of origin. Mitochondrial and nuclear DNA sequence data from the samples of D. nordmannianae collected in its native range and Europe and from the samples of Dreyfusia piceae and Dreyfusia prelli collected in Europe and North America were examined for phylogenetic structure. There was no evidence of differentiation, suggesting that these Dreyfusia species have recently diverged or require taxonomic revision. All existing published and unpublished reports on natural enemies of D. nordmannianae in its place of origin were reviewed, with the purpose of selecting agents for classical biological control in Europe. The literature review suggested that the most promising agent was the Chamaemyiidae fly, Leucopis hennigrata. A new survey in D. nordmannianae's area of origin – Turkey, Georgia and Russia – showed that L. hennigrata was present in all localities. It was particularly abundant in Turkey, where its impact on populations of D. nordmannianae appears to be high. Its use as a biological control agent is discussed, as well as other biological control strategies.